In vitro leakage associated with three root-filling techniques in large and extremely large root canals - Mente, Johannes; Werner, Sabine; Koch, Martin Jean; Henschel, Volkmar; Legner, Milos; Staehle, Hans Jörg; Friedman, Shimon (Journal of endodontics, 2007)
This study assessed the apical leakage of ultrasonically condensed root fillings in extremely large canals, compared to cold lateral condensation and thermoplastic compaction.